Evidence of Pulmonary Vascular Reverse Remodeling After Pulmonary Artery Banding Performed in Early Infancy in Patients With Congenital Heart Defects - Kawamoto, Shunsuke; Saiki, Yoshikatsu; Saiki, Yuriko; Akiyama, Masatoshi; Maeda, Kay; Masaki, Naoki; Adachi, Osamu; Endo, Masato (Circulation Journal, 2018)
Background:Histomorphometric evidence of the effect of pulmonary artery banding (PAB) in infancy on pulmonary vascular reverse remodeling has not been fully described.Methods and Results:We retrospectively reviewed 34 patients who underwent serial lung biopsies before and after PAB.Index of pulmonary vascular disease (IPVD) as a measure of the degree of progression of pulmonary arteriopathy significantly decreased after PAB (1.22±0.25 at 1st and 1.13±0.21 at 2nd biopsy, P=0.04). Additionally,DR=100 µmas an indicator of medial thickness of pulmonary arteries significantly decreased after PAB (15.6±3.7 at 1st and 11.4±2.6 at 2nd biopsy, P<0.0001). Patients were divided into 3 groups by age at PAB: <3 months (Group 1), between 3 and 6 months (Group 2), and >6 months (Group 3). The average secondDR=100 µmof groups 1 and 2 was significantly lower than that of group 3 (11.1±2.2 and 9.8±2.0 vs. 14.9±2.8, respectively; P<0.0001). Additionally, the second IPVD was also significantly lower in groups 1 and 2 than in group 3 (1.1±0.2 and 1.1±0.2 vs. 1.3±0.4, respectively; P=0.02).Conclusions:Histomorphometric evidence of post-PAB pulmonary vascular reverse remodeling is robust. The magnitude of vascular reversibility is pronounced when PAB is performed before 6 months of age.